Papel dos níveis séricos de vitamina d e da síndrome metabólica e o risco de câncer de mama - Fernandes, Eveline Maria Aragão (2020)
Introduction: Breast cancer is the most common neoplasm in the female population and several modifiable and non modifiable factors are ass ociated with increased risk. Among these modifiable factors, levels of vitamin D and metabolic syndrome are associated, although not yet well defined, in relation to the risk of breast cancer. Objectives: To evaluate the relationship of serum vitamin D lev els and metabolic syndrome with breast cancer risk in Brazilian women, and their clinical, histopathological and immunohistochemical characteristics. Methodology: Case control study included 92 women, between May 2019 and March 2020. Participants were divi ded into two groups: cases ( 42 women with breast cancer) and control ( 50 women without cancer). Each woman was interviewed and investigated for serum levels of 25 (OH) D through blood collection, using the chemiluminescence method, and for metabolic syndro me using the criteria of the International Diabetes Federation (IDF). In the case group, clinical, histopathological and immunohistochemical characteristics were also investigated. From the data obtained, the chi square test or Fisher's test was applied wh en proper. Student's t test was performed to compare vitamin D concentrations and the logistic regression model assessed the risk of breast cancer, with vitamin D and metabolic syndrome as an exposure. It was considered P <0.05 as significancy. Results : Th e average of vitamin D levels was higher in the cases group than in the control (26.3 ng / mL x 24.1 ng / ml), with no statistical difference (p = 0.141). Metabolic syndrome was common in women with breast cancer, compared to controls (64.3% x 62.0%), but without statistical significance (p = 0.821). Regarding to the individual criteria for metabolic syndrome, there was no statistical difference between groups in relation to waist circumference (p = 0.750), plasma glucose (p = 0.542), triglycerides (p = 0.2 35), HDL (p = 0.144) and blood pressure (p = 0.193). Hypovitaminosis D and/or metabolic syndrome had no statistical significance in relation to clinical, histopathological and immunohistochemical characteristics in patients with breast cancer. There was al so no association between vitamin D levels and/or metabolic syndrome for breast cancer risk and with prognostic markers (clinical staging and immunohistochemical subtypes). Conclusion: Vitamin D levels and metabolic syndrome were not associated with a high er risk of breast cancer and there were no relation to their clinical, histopathological and immunohistochemical characteristics.